An overview of possible pivotal mechanisms of Genistein as a potential phytochemical against SARS‐CoV‐2 infection: A hypothesis. Issue 10 (22nd July 2022) - Jafari, Abbas; Esmaeilzadeh, Zeinab; Khezri, Mohhamad Rafi; Ghasemnejad‐Berenji, Hojat; Pashapour, Sarvin; Sadeghpour, Sonia; Ghasemnejad‐Berenji, Morteza
Abstract: The Coronavirus Disease 2019 (COVID‐19) pandemic has been caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). It is a global problem that humanity has not yet found a definitive solution for it. In this regard, a global effort has been done to find effective or potential adjuvant therapies in order to fight this infection. Genistein is a small, biologically active phytoestrogen flavonoid that is found in high amounts in soy and plants of the Fabaceae family. This important compound is known due to its anti‐cancer, anti‐inflammatory, and antioxidant effects. Additionally, protective effects of genistein have been reported in different pathological conditions through modulating intracellular pathways such as PI3K, Akt, mTOR, NF‐κB, PPARγ, AMPK, and Nrf2. Scientific evidence suggests that genistein could have a potential role to treat COVID‐19 through its anti‐inflammatory and anti‐oxidant effects. Furthermore, it appears to interfere with intracellular pathways involved in viral entry into the cell. This review provides a basis for further research and development of clinical applications of genistein as a potential alternative therapy to decrease inflammation and oxidative stress in COVID‐19 patients. Practical applications: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), the etiological agent for the Coronavirus Disease 2019 (COVID‐19), has brought unprecedented untold hardship to both developing and developed countries. The inflammation, cytokine storm, and oxidative stress have an important role in the pathogenesis of this infection. In this regard, finding plant‐derived compounds with anti‐inflammatory and anti‐oxidative effects would be very beneficial in reducing the mortality induced by this infection. Genistein an isoflavone derived from soy‐rich products possesses versatile biological activities. It has potent anti‐inflammatory and anti‐oxidative and immunomodulatory effects. Furthermore, this compound may prevent viral entry to host cells and reduce SARS‐CoV2‐induced lung injury. Therefore, we suggest further studies on the effects of genistein on SARS‐Cov‐2 infection. Abstract : The probable beneficial effects of genistein in COVID‐19.